Temporary Partial Periosteal Graft for Emergency Management in Peripheral Corneal Perforation: Poster Presentation - Case Report - Resident - Indah Saraswati; Ridho Ranovian; Yulia Aziza; Astrianda Nadya Suryono (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal perforation occurs secondary to a number of corneal abnormalities and leads to further complications if left untreated. Varies options for managing corneal perforation had been conducted, yet the data of periosteal graft in ophthalmology was still limited. This case report aims to evaluate the efficacy of periosteal graft in peripheral corneal perforation. Case Illustration : A 77-year-old female patient came with a chief complain 14-day history of severe ocular pain and blurry vision of left eye. Initially, there were recurrent ocular redness with foreign body sensation since 6 month before admission, yet denied any history of systemic and autoimmune diseases. She was assessed as corneal infection by some hospitals and treated with some medications, yet the symptoms were not improved. The ophthalmological examination revealed a 360 degrees corneal thinning with uveal prolapse on the infero-temporal on limbus part. The perforation was treated with partial periosteal graft and conjunctival resection, as the corneal donor for tectonic keratoplasty was not available. A few months after surgery, the grafts remained in place after the surgery, even though the visual acuity was still the same. Discussion : Because of its ease in harvesting, avascularity, strength and lack of immune reaction, autogenous periosteum is a potential grafting tissue for corneal covering in the case of corneal perforation, although it was not the gold standard treatment. This technique presented satisfactory results with low complication rates and minimum number of complications. Conclusion : Temporary partial periosteal graft could be considered as emergency surgical options in peripheral corneal perforation.